Internet of Things-Based Home Trash Capacity Tracking System with Instant Notifications - Munthe, Era Sari; Diantoro, Karno; Herwanto, Agus (Digitus : Journal of Computer Science Applications, 2024)
Garbage created from routine household activities is collected and stored in household garbage cans. Location This garbage makes rubbish collection easier to live in and helps to maintain a clean household environment. Household garbage cans are often designed to fit specific demands and feature a tight-fitting cover to keep sickness and animals out and to minimize unwanted odors. The layout To stop the spread of bacteria or fungus, something must be easy to clean. Lack of technology to monitor garbage bin fullness and inability to precisely monitor fill capacity, which can lead to trash overflow, offensive odors, and animal nuisances. Thus, volume sensorization techniques and Internet of Things (IoT) technologies are the answers to this challenge. To enable real-time waste capacity volume monitoring and to give users level information about trash charging through the Blynk platform, the system will deliver When the garbage can is full, an alarm sensor-equipped warning will ring. The Arduino IDE and the C programming language are the software used. The findings of the study demonstrate that the garbage can capacity monitoring system The information about waste filling levels that are provided in real-time by this IoT-based system is effective. By using this approach, homeowners can easily keep a clean and healthy home environment by knowing when it's time to remove the trash.